Exploring ethical requirements elicitation for applications in the context of AI - Cerqueira, José Antonio Siqueira de (2021)
Dissertação (mestrado)—Universidade de Brasília, Instituto de Ciências Exatas, Departamento de Ciência da Computação, 2021.